Effect of smoking on neutrophil apoptosis in chronic periodontitis: An immunohistochemical study - Sachin S Shivanaikar; Mohamed Faizuddin; Kishore Bhat (Wolters Kluwer Medknow Publications, 2013)
Context: Periodontal disease is caused by chronic infection inducing an inflammatory reaction leading to breakdown of tooth-supporting tissues. There are various risk factors for the disease, and smoking is one of them. Apoptosis plays a critical role in the regulation of inflammation and host immune response which helps in tissue homeostasis, and a disturbance in this is often associated with disease. The imbalance between the apoptosis and proliferation in the periodontal tissue results in periodontal disease. Neutrophils play an important role in the defense mechanism and are the most abundant immune cells in gingival inflammatory infiltrate in patients suffering from periodontal disease. Neutrophil disorders are associated with rapid destruction of periodontal tissues. Aim: To study the influence of smoking on apoptosis of neutrophils by quantifying them in the gingival connective tissue of smoking and nonsmoking subjects suffering from chronic periodontitis. Materials and Methods: Thirty gingival biopsies were harvested from 15 smoking and 15 nonsmoking subjects who suffered from chronic periodontitis. The apoptosis of neutrophils was assessed and quantified using p53 monoclonal mouse antihuman antibody. Statistical Analysis Used: Chi-square/Fisher'sexact test was used to find the significance of study parameters on a categorical scale between the two groups. Results: Neutrophil apoptosis was significantly more in the group of nonsmokers. There was no statistical difference between plaque and bleeding index, but there was a significant increase in clinical attachment loss among smokers. Conclusions: The study reveals that smoking plays a significant role in the inhibition of neutrophil apoptosis, thereby contributing to the destruction of periodontal tissues in periodontitis.